Shoreline dynamics during 1972–2022, and ITS implications, Vedaranniyam region, Tamil Nadu, India - A. Vijay; J. Saravanavel; S. M. Ramasamy; S. Vasudevan (Discover Geoscience)
Abstract Due to the continuous interface dynamics amongst tectonic, fluvial, coastal and aeolian geomorphic processes, the coastal zones always remain dynamically active with resultant morphological changes like land building and land loss activities. Such morphological changes along the coasts do also control the environment of the coastal systems. In this connection, the east coast of India is unique with complex tectonic and geomorphic processes and the resultant dynamically changing coastal morphologies. Amongst various local processes like wind, wave, tides and the eddies, the regional component of the littoral current is one of the dynamic processes along the east coast of India which move northerly from Cape Comorin in the south to West Bengal coast / Sundarbans in the north during the non-northeast monsoon months (Mar–Oct). These again move southerly all along the east coast of India from the West Bengal coast in the north to Cape Comorin in the south during the northeast monsoon months (Nov-Feb). These currents cause sediment dump in the current ward side and the coastal erosion in the current shadow side when the littoral currents are obstructed by promontories or manmade projections all along the east coast of India. In this connection, detailed mapping of the shorelines and there from the spatial estimation of the erosion/deposition was carried out for the Vedaranniyam region using the satellite Infra-Red & Near Infra-Red data for the years 1972, 1997, 2004, 2006, 2009, 2016, 2018 and 2022. Infrared band of Landsat data was used to demarcate the land–water boundary. In infrared region water bodies exhibit the darker tone with smooth texture to absorption and at the same time, due to heterogeneity, the land portion showing the coarser texture with varying reflectance. This is very much helpful in delineating land–water boundary in general. These showed that the land has grown by an average area of 1.27 km2 in fifty years from 1972 to 2022 in the central Vedaranniyam nose region. Whereas, there observed the land loss or erosion on the northern and southern parts of Vedaranniyam. Keeping this as the base value, the areal extent of land growth was visualised for every 500 years viz. 2500, 3000, 3500, 4000 AD and so on. This indicated that, under the prevailing littoral current dynamics and the seabed topography observed from GEBCO data in between the Vedaranniyam nose (India) and Jaffna peninsula (Sri Lanka), the land will get connected by a land bridge between the both in another 10,000 or 12,000 years. Such land bridging may also lead to the formation of a protected sea in between Vedaranniyam—Jaffna sector in the north and Ramanathapuram—Rameswaram—Thalaimannar sector in the south.This may also end up with the formation of a land in due course of time in such a protected sea due the sediment dump from the rivers of the southernmost part of Tamil Nadu.